Wierność charyzmatowi a lojalność wobec państwa – – posłannictwo salezjańskie pod rządami ks. generała Michele Rua - Zimniak, Stanisław (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The intervention intends to analyze how the Salesian works have joined fi delity to the Salesian charism with the need to respect the different political frameworks in which they find themselves, documenting how the educational mission has never lacked loyalty towards those States in which they exist or those into which it intended to expand. The historical survey suggested here, is limited to the Old Continent and more precisely to the Central European basin, for various reasons. The issue set is not becoming the subject of a monographic study. Through the analysis of some facts they will try to present the attitude and conduct of the Rector Major of the Salesian Congregation, Fr Michele Rua, and of the Salesians and in this respect, focusing attention primarily on external evaluations of their apostolate. This setting attempts to answer basic questions: Can a religious institution, although driven by determination to remain faithful to the charism and despite its declared apolitical attitude, operate without being involved in the political dimension? Doesn’t it seem utopian to think that a religious congregation, all the more so with the size of the Salesians, can avoid being perceived in terms of its political signifi cance?